Optical Model for Simulation and Optimization of Luminescent down-shifting Layers in Photovoltaics. (December 2015) - Lipovšek, Benjamin; Solodovnyk, Anastasiia; Forberich, Karen; Stern, Edda; Brabec, Christoph J.; Krč, Janez; Topič, Marko
Abstract: We present an optical model that was developed for the purpose of simulation and optimization of luminescent down-shifting layers based on phosphor particles. The model combines three-dimensional ray tracing with a novel effective scattering approach based on the Mie scattering theory. Verification of the model with experimental results shows that the model accurately takes various layer parameters into account, such as the layer thickness, the phosphor volume concentration, and the phosphor particle size distribution. Finally, using the verified model, we investigate the concept of luminescent down-shifting in organic solar cells and discuss the optimal layer parameters. Preliminary simulation results show that in the case of the studied solar cell, an improvement in the short-circuit current density of more than 6% can be obtained.